2020
DOI: 10.1177/1470320320919610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various confirmatory tests for the diagnosis of aldosterone-producing adenoma

Abstract: Introduction: Adrenal venous sampling is useful for discriminating unilateral and bilateral hypersecretion in patients with primary aldosteronism, but it is relatively invasive. To determine the site of hypersecretion more non-invasively, we evaluated predictors of unilateral hypersecretion. Materials and methods: We evaluated the baseline characteristics and the results of confirmatory tests of 123 patients with primary aldosteronism who underwent adrenal venous sampling. Results: Unilateral hypersecretion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…We restricted studies to those with a sample size ≥10 (to avoid case reports) and written in English. Flow of studies through review and summary of the identified 9 studies are shown in Figure 1B and Table 2 (17)(18)(19)(49)(50)(51)(52)(53)(54).…”
Section: Acth Stimulation Test For the Diagnosis Of Primary Aldosteromentioning
confidence: 99%
See 1 more Smart Citation
“…We restricted studies to those with a sample size ≥10 (to avoid case reports) and written in English. Flow of studies through review and summary of the identified 9 studies are shown in Figure 1B and Table 2 (17)(18)(19)(49)(50)(51)(52)(53)(54).…”
Section: Acth Stimulation Test For the Diagnosis Of Primary Aldosteromentioning
confidence: 99%
“…In 1995, Stowasser et al reported higher plasma aldosterone response after ACTH stimulation under dexamethasone suppression among angiotensin II responsive APA (n=16) or angiotensin II unresponsive APA (n=11) compared with BAH (n=19) (55). Although several studies mostly from Japan have shown moderate to high predictive performance (area under the curve [AUC] ranges from 0.70 to 0.95) to differentiate APA from BAH by using ACTH stimulation test (17,18,(49)(50)(51)(52)54) over the last two decades, these findings are not comparable across studies due to the lack of uniformity in protocols in each study (e.g., ACTH dosage, with or without 1 mg DST, different cut-off time or values, etc), inconsistent definition of outcomes (e.g., diagnosis of APA and BAH based on AVS, histopathological findings, etc. ), and study design (sample size, single-center or multi-center, prospective or retrospective, etc.).…”
Section: Acth Stimulation Test For the Diagnosis Of Primary Aldosteromentioning
confidence: 99%
“…All included patients met the criteria of adrenal PAC ! 14,000 pg/mL in the unilateral or bilateral adrenal veins after ACTH stimulation, as in our previous studies (15,16). Unilateral aldosterone hypersecretion was diagnosed if the lateralized ratio, calculated as the adrenal vein A/C ratio on the high-value side/low-value side, was !…”
Section: Study Populationmentioning
confidence: 84%
“…A total of 95 patients who presented to our center between April 2011 and March 2022 with a final diagnosis of PA and who met the criteria of plasma aldosterone concentration (PAC) >120 pg/mL, aldosterone renin ratio (ARR) > 200, and positivity on at least one confirmatory test (captopril challenge test [CCT], upright furosemide loading test, or saline loading test) based on the JSH2019 guideline were included, as in our previous studies (14)(15)(16). Patients treated with vitamin D3 were excluded.…”
Section: Study Populationmentioning
confidence: 99%